Resistance to Computerized Care Planning Systems by Qualified Nurses Working in the UK NHS - Timmons, S. (Methods of Information in Medicine, 2003)
Objective: This study investigated whether computerized systems, designed to produce detailed plans for the nursing care of inpatients, were resisted by the nurses who were expected to use them.Methods: Qualitative study, using semi-structured interviews with nurses working in the UK National Health Service.Results and Conclusions: Resistance took the form of ‘resistive compliance,’ and this resistance is analyzed and explained. Resistance can best be understood in terms of the culture of nursing. This implies that the design and implementation of computerized systems in health care should take these factors into account.
Keywords: Resistance; nursing informatics; nurses